A multidimensional approach to talent identification and selection in high-level youth Australian Football players - Tribolet, R.; Bennett, K. J. M.; Watsford, M. L.; Fransen, J. (Journal of Sports Sciences, 2018)
There is limited research in talent identification in youth Australian Football (AF), especially the factors that underpin selection into higher-level development programs. Therefore, this study explored age-related differences in high-level youth AF players and investigated characteristics influencing selection into a high-level development program. Anthropometry (stature, sitting height, body mass), maturity (estimated age at peak height velocity), motor competence (Körperkoordinationstest für Kinder), fitness (change of direction speed, lower body power and upper body muscular endurance) and coach skill ratings (kicking, marking and handballing) of 277 state academy players (U13-U15) were assessed. MANOVAs identified significant age-related differences for anthropometry, fitness, and coach skill ratings. Furthermore, 90.9 and 90.0% of U15 selected and deselected players were classified correctly. Selected players were more mature, taller, heavier, more explosive, faster at changing directions, and had superior kick technique and marking results. These results demonstrate considerable age-group performance outcome differences, highlighting that high-level academies should aim to select or deselect after 15 years of age. Additionally, it appears earlier maturing players are favoured for selection into a high-level academy. While practitioners must consider the confounding effect of maturation, early maturing players may be favoured for their ability to withstand increasing demands in higher-level youth AF.